Some fishing methods of Iloilo and Capiz - Baylon, Rafael T. (College of Fisheries, University of the Philippines, 1953)
Iloilo is one of the most important commercial fishing centers of Western Visayas. Capiz, due to the discovery of its trawling grounds is now becoming an important fishing center as well. The conditions obtaining in these places are suitable for the growth and development of some commercial fisheries, the most important of which are the sardines, anchovies and mackerels for the pelagic gear and big slipmouths, nemiptherids, and others for the demersal gear. Following loberation, when almost everybody used explosives for fishing, fisheries in the area suffered decrease due to such an extent as to alarm the populace. Our aim therefore is to eliminate this destructive gear and use the profitable commercial fishing methods as described in this report. Among the many fishing methods found in these localities, are the bag net (basnig), sapiao, and otter trawl are the most important. Crab pots and push net are the important sustenance fishing engaged into by the common fishermen lacking the capital to engage in the more promising and commercial gear. The bag net is now becoming the most common and most profitable pelagic fishing gear, while the otter trawl the most important demersal method. The sapiao aside from being one of the oldest pelagic methods has not lost its importance especially in the capture of anchovies in Iloilo and Capiz.